Методи підвищення морозо-, зимостійкості пшениці м’якої озимої (Triticum aestivum L.) в умовах Лісостепу України - Кириленко, В.В.; Гуменюк, О.В.; Дергачов, О.Л.; Дубовик, Н.С.; Близнюк, Б.В.; Хоменко, С.О. (Фактори експериментальної еволюції організмів, 2015)
Aims. Installing the correlation between the main indicator productivity — seed weight per plant and other quantitative traits of soybean; study the effectiveness of selection on one of the selective traits in hybrids F3 –F5 of soybeans. Methods. The study was conducted in hybrid and breeding nurseries of soybean of Institute of irrigated agriculture NAAS for 2007–2009, growing technology is common for irrigation conditions of southern Ukraine. The generalization of correlation coeffi cients quantitative traits was performed by the method of J. William Snedekor; bonding force was determined by B. Dospyehov. Results. We have analyze a correlations between weight of seeds per plant (the basic index of productiveness) and other quantitative trait of soybean; selection effectiveness for productivity of soybean hybrid populations F3 –F5 by number of productive nodes from plant. There are the characteristics of new soybean varieties that had made by improved method of selection in the article. We have received the positive average correlation between weight of seeds per plant and stem thickness, stem bottom thickness, quantity of branches on the plant and number of productive nodes on a main stem. We have obtained strong correlation between weight of seeds per plant and number of productive nodes on branches, productive nodes on a plant, bean’s quantity per plant, quantity of seeds per plant, plant weight and weight of beans. Conclusions. Signs that had a strong positive correlation with seed weight per plant, we can assume factorial and apply in the selection to improve productivity of soybean. Selection on the number of productive nodes on the plant are most effective for increasing seed mass per plant. Keywords: soybean, hybrids, selection, correlation, seed weight.